Expanding Narrative Medicine: Four Notes - Dalrymple-Fraser, C (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Considering the possible futures of bioethics invites us to interrogate our existing theories and methods. This text focuses on futures for narrative medicine, offering four notes for an expanded practice. Specifically, I argue that future work in narrative medicine can further benefit from interrogating the scopes, archives, and methodologies of narrative medicine, and investing in material supports.